Flood Risk Analysis Integration of Land Use Change, RTRW Suitability, and Vulnerability in the Jang River Watershed, Tanjung Pinang City - Aldina Febriany; Ratna Wilis; Nofrion; bin Fauzi, Rosmadi (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This study aims to comprehensively analyze flood risk by integrating spatial dynamics such as land use changes, regional spatial planning policies (RTRW), and flood hazard and vulnerability levels in the Sungai Jang watershed, Tanjung Pinang City. This study uses a spatial quantitative approach based on Geographic Information System (GIS) and weighted overlay techniques. This study found a strong causal relationship between land use change and an increase in flood risk. In the period 2017 – 2025, there was a decrease in hydrological function due to an increase in built-up area of around 20.89% and a shrinkage of productive areas, including wetland vegetation, which decreased by 54% from 2021. This change in land use results in a moderate flood hazard area of 4,442.01 hectares and a height of 306.83 hectares. The land mismatch with the RTRW of 6,206.61 hectares indirectly puts it in a flood risk area. The level of vulnerability with the criteria of prone pants is 426.34 hectares, and the criterion of very vulnerable is found in areas that are undergoing development that are not in accordance with the spatial planning of the region.